Analisis Pengaruh Ratio Keuangan dengan Harga Saham pada Perusahaan Properti di Bursa Efek Indonesia - Bambang Sugeng Dwiyanto (Universitas Proklamasi 45 Yogyakarta, 2012)
Bankcruptcy is a very important problem, in which every company should be aware of. It is very important to detect the signs of the coming bankruptcy of the company as soon as possible in order to take effective action to avoid it. One popular model to do so is Z-score, a statistical model to predict bankruptcy based on company financial performance. This paper deals with the analysis of the financial performance of property companies listed on the Indonesia Stock Exchange. However, in previous research it was found that there is no strong correlation between the companies financial performance with their stock prices, thus encouraging further research. In this research, the analysis focused on the influence of the financial ratio-ratio (X1) Ratio net working capital / total assets, (X2) Ratio of retained earnings / total assets, (X3) Ratio of earnings before interest and taxes / total assets, (X4) Ratio of market value equity / book value of total debt, and (X5) Total sales / Total assets) to the stock price. Apparently based on classical assumption test, multiple regression analysis, coefficient of determination, and F-Test , it was found that there is no significant effect between the financial value of ratio-ratio simultaneously with their stock prices, and the ratio of total sales / total assets is the most dominant variable influence.